The behavior of brazilian senators: analyzing the exchange of votes inside the fixed committees during the 52nd legislature - Mauerberg Júnior, Arnaldo; Strachman, Eduardo [UNESP]; Reami, Daniela de Oliveira (Universidade Federal do Paraná, 2013)
Using the method of Social Networks Analysis, we’ll try to see if politicians swap votes between them seeking support for their projects, to this end, we’ll first map the behavior, activities and contacts of the Senators of the Brazilian Federative Republic within all the fixed committees which had some vote during the 52nd Legislature, then we can see the most popular and central Senators to each committee. After this analysis we wish to answer the following question: did logrolling exist in the Brazilian Senate? Previously the empirical analysis and response to the problems posed, we’ll present the necessary theoretical introduction understood by reviewing the literature on relevant subjects, whether they are purely theoretical with respect to the exchange of support, or analytical about the Brazilian political system.

Utilizando a metodologia de Análise de Redes Sociais, intentamos analisar se os políticos brasileiros trocam votos na aprovação de projetos de lei em busca de apoio futuro. Para tanto, buscamos primeiramente mapear o comportamento, a atuação e os contatos dos Senadores da República Federativa do Brasil dentro das comissões fixas que tiveram qualquer movimentação durante a 52ª Legislatura, poderemos então ver quais são os Senadores mais atuantes e centrais em cada comissão. Após este mapeamento procuramos criar meios de análise para responder a questão teórica da existência ou não do logrolling no Senado Brasileiro. Anteriormente a análise empírica e resposta aos problemas propostos, apresentaremos a devida introdução teórica compreendida por uma revisão de literatura sobre os temas pertinentes, sejam eles puramente teóricos a respeito da troca de apoio, sejam eles analíticos a respeito do sistema político brasileiro.
O comportamento dos senadores brasileiros: analisando a troca de votos nas comissões fixas durante a 52ª legislatura
Keywords: Logrolling; Legislative Activity; Brazilian Senate; Social Networks Analysis; Troca de Votos; Atividade Legislativa; Senado Brasileiro; Análise de Redes Sociais